Phasing and climate forcing potential of the Millennium Eruption of Mt. Baekdu. - Lee, Giyoon; Burke, Andrea; Hutchison, William; Sugden, Patrick; Smith, Celeste; McConnell, Joseph R; Sigl, Michael; Oppenheimer, Clive; Rasmussen, Sune Olander; Steffensen, Jørgen Peder; Lee, Seung Ryeol; Ahn, Jinho (Springer Science and Business Media LLC, 2024)
Funder: Basic Research Project (GP2021-006) of the Korea Institute of Geoscience and Mineral Resources (KIGAM) funded by the Ministry of Science, ICT of Korea; EPSRC Light Element Analysis Facility Grant (EP/T019298/1); Strategic Equipment Resource Grant (EP/R023751/1); U.S. National Science Foundation grants (1023672 and 1925417); Villum Investigator Project IceFlow grant (16572); Philip Leverhulme prize in Earth Sciences (PLP-2021-167); UKRI Future Leaders Fellowship (MR/S033505/1); European Research Council under the European Union’s Horizon 2020 research and innovation program (grant agreement no. 820047) The Millennium Eruption of Mt. Baekdu, one of the largest volcanic eruptions in the Common Era, initiated in late 946. It remains uncertain whether its two main compositional phases, rhyolite and trachyte, were expelled in a single eruption or in two. Investigations based on proximal and medial ash have not resolved this question, prompting us to turn to high-resolution ice-core evidence. Here, we report a suite of glaciochemical and tephra analyses of a Greenlandic ice core, identifying the transition from rhyolitic to trachytic tephra with corresponding spikes in insoluble particle fallout. By modeling annual snow accumulation, we estimate an interval of one to two months between these spikes, which approximates the hiatus between two eruptive phases. Additionally, negligible sulfur mass-independent fractionation, near-synchroneity between particle and sulfate deposition, and peak sulfur fallout in winter all indicate an ephemeral aerosol veil. These factors limited the climate forcing potential of the Millennium Eruption.